Inovasi Pembuatan Canting Batik Elektrik Solusi Modern untuk Pengrajin Batik di Pekalongan - Nabila Yudisha; Adam Cahya Soeprapto; Nashwa Bayu Tsabitha (Universitas Maritim AMNI Semarang, 2024)
By modifying three traditional canting designs using the House of Quality (HoQ) method, this article discusses the development of a portable electric canting. The main focus of this research is to use electrical technology to improve the convenience and efficiency of the batik-making process. Each new design has a recharging system that allows the user to recharge the power source. User needs and wants were discovered and incorporated into the technical specifications of each design through HoQ analysis. Research shows that these changes not only improve tool performance but also make the batik-making process safer and more environmentally friendly. Therefore, through the development of relevant and sustainable technologies, this project contributes to the preservation of Indonesia's batik culture.